2016
DOI: 10.3171/2016.4.spine151481
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory evoked potential monitoring detection of carotid compression during ACDF surgery in a patient with a vascularly isolated hemisphere

Abstract: The authors report herein a case of anterior cervical discectomy and fusion (ACDF) surgery in which findings on somatosensory evoked potential (SSEP) monitoring led to the correction of carotid artery compression in a patient with a vascularly isolated hemisphere (no significant collateral blood vessels to the carotid artery territory). The amplitude of the cortical SSEP component to left ulnar nerve stimulation progressively decreased in multiple runs, but there were no changes in the cervicomedullary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…MEPs are also highly sensitive (100%)14 whereas SSEPs are much less so (17.7%–35.2%) 14,23. Case reports describe unique situations, in which IONM detected arterial compression and brachial plexopathy due to shoulder traction 25,26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MEPs are also highly sensitive (100%)14 whereas SSEPs are much less so (17.7%–35.2%) 14,23. Case reports describe unique situations, in which IONM detected arterial compression and brachial plexopathy due to shoulder traction 25,26…”
Section: Discussionmentioning
confidence: 99%
“…14,23 Case reports describe unique situations, in which IONM detected arterial compression and brachial plexopathy due to shoulder traction. 25,26 Several database studies have been performed similarly to our investigation. Cole and colleagues performed a retrospective analysis using the MarketScan national database of single-level spinal procedures including ACDF, lumbar laminectomy, lumbar discectomy, and lumbar fusion between 2006 and 2010.…”
Section: Intraoperative Neuromonitoring Utilizationmentioning
confidence: 99%
“…Cervical traction (5-15 lbs) may be appropriate, especially in cases of intervertebral disk degeneration. Intraoperative monitoring, including somatosensory and transcranial motor evoked potentials, is recommended as it may help to prevent iatrogenic injury to the spinal cord or roots (Davis et al 2013;Legatt et al 2016).…”
Section: Surgery Positioning and Monitoringmentioning
confidence: 99%
“…Legatt et al 22 reported a case of anterior cervical discectomy and fusion surgery in which findings on somatosensoryevoked potential monitoring led to the correction of carotid artery compression in a patient with a vascularly isolated hemisphere (no significant collateral blood vessels to the carotid artery territory), and the patient suffered no neurological morbidity. During anterior cervical spine surgery, carotid artery compression by the surgical retractor can cause hemispheric ischemia and infarction in patients with inadequate collateral circulation.…”
Section: Anterior Fusionmentioning
confidence: 99%